2020
DOI: 10.3390/bioengineering7030076
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Injury Models to Study Skeletal Muscle Regeneration and Repair

Abstract: Skeletal muscle injuries that occur from traumatic incidents, such as those caused by car accidents or surgical resections, or from injuries sustained on the battlefield, result in the loss of functionality of the injured muscle. To understand skeletal muscle regeneration and to better treat these large scale injuries, termed volumetric muscle loss (VML), in vivo injury models exploring the innate mechanisms of muscle injury and repair are essential for the creation of clinically applicable treatments. While t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…Several other approaches are possible to achieve clinically applicable treatments of muscle injuries such as understanding the underlying mechanisms of muscle loss or repair, exploration of a new drug, and evaluation of biocompatibility or biofunctionality of materials. [74,75] To improve scaffold-or cell-based intervention, Sicherer et al directly compared different muscle loss models [76]. Here, we elucidated the advantages and characteristics of engineering techniques of skeletal muscle tissue focused on the fabrication method, material properties, and evaluation methods.…”
Section: Discussionmentioning
confidence: 99%
“…Several other approaches are possible to achieve clinically applicable treatments of muscle injuries such as understanding the underlying mechanisms of muscle loss or repair, exploration of a new drug, and evaluation of biocompatibility or biofunctionality of materials. [74,75] To improve scaffold-or cell-based intervention, Sicherer et al directly compared different muscle loss models [76]. Here, we elucidated the advantages and characteristics of engineering techniques of skeletal muscle tissue focused on the fabrication method, material properties, and evaluation methods.…”
Section: Discussionmentioning
confidence: 99%
“…This section aims at providing an overview of the cellular strategies that have been developed for improving skeletal muscle regeneration in mammals, particularly humans. As for the methods employed to study skeletal muscle regeneration, readers can refer to more comprehensive reviews [ 7 , 223 , 225 , 226 , 227 ].…”
Section: Mammals: Cell Therapy For Skeletal Muscle Regenerationmentioning
confidence: 99%
“…Nowadays, only few animal models (mainly rodents, chicken, and to some extent zebrafish) have been suitably exploited in muscle regeneration studies and various injury protocols (e.g., surgery, chemically induced muscle damage, genetic ablation, denervation-devascularization, intensive exercise, etc.) have been employed [ 178 , 225 , 226 , 247 , 248 , 249 ]. Except for zebrafish, none of the animal species presented in this review have been systematically tested for the efficacy and utility of the diverse injury models; indeed, the main methods employed to stimulate regeneration are based on physically- (by surgery or irradiation) and chemically-induced muscle damage, and genetic ablation.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Studies from numerous groups have demonstrated that muscle tissue repair is a complex phenomenon involving degeneration, inflammation, regeneration, and fibrosis, which are continuous processes with significant overlap [ 6 , 7 ]. Muscle injury models are being developed to improve understanding of how tissues respond to injuries caused by mechanical stress [ 8 ].…”
Section: Introductionmentioning
confidence: 99%